Pancasila as an Islamic Ideology for IndonesianMuslim: An Interview with Munawir Sjadzali - Prasetyo, Hendro (Studia Islamika, 1994)
The independence of Indonesia created a new political horizon. The shift from old political systems such as ethnicity-based, monarchic or colonial, to a nation-state has been an invaluable experience for Indonesians. They started to live in a pluralistic society and within new international relationship. BUt given the fact  that the new system was embryonic and different from the oldones, Indonesians also experienced intricate frictions in both political and spheres.  Conflicts of interests, wheter religious, classbased or cultural, became an inseparable part of the political process.DOI: 10.15408/sdi.v1i1.871